2015
DOI: 10.1123/jpah.2012-0339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home-Based Walking on Quality of Life and Fatigue Outcomes in Early Stage Breast Cancer Survivors: A 12-Week Pilot Study

Abstract: Background: Adjuvant treatment for breast cancer may result in long-lasting, adverse emotional and physical side effects, and reduce quality of life (QOL). This pilot study examined the effects of a home-based walking program on QOL and fatigue in early stage breast cancer survivors and whether changes in walking behavior were associated with changes in outcomes. Methods: Participants (n = 32) were randomized to a 12-week home-based walking intervention plus brief telephone counseling (n = 20) or a wait-list c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(94 citation statements)
references
References 26 publications
0
91
1
2
Order By: Relevance
“…28 This form of PA is popular and inexpensive, and can be applied in women with BC. 10,29 It can be an option for alleviating the adverse side effects of BC treatment, improving the QOL and minimizing fatigue symptoms. 29 The present study, showed that Brazilian women with BC did not achieve the amount of PA required.…”
Section: Discussionmentioning
confidence: 99%
“…28 This form of PA is popular and inexpensive, and can be applied in women with BC. 10,29 It can be an option for alleviating the adverse side effects of BC treatment, improving the QOL and minimizing fatigue symptoms. 29 The present study, showed that Brazilian women with BC did not achieve the amount of PA required.…”
Section: Discussionmentioning
confidence: 99%
“…Some results of previous studies demonstrated that exercises may improve muscle strength and cardiorespiratory endurance in BC patients during rehabilitation and further improve their emotions and QOL [5,[7][8][9][10][11][12]. However, there are some problems in the current exercise rehabilitation forms.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure consistency in intervention delivery across sessions and participants, a semistructured motivational interviewing-based intervention protocol was developed to guide intervention delivery. The topics covered in the 30-45 min consultation were similar to other trials (Baruth, Wilcox, Der Ananian, & Heiney, 2015;Matthews et al, 2007;Pinto et al, 2005;Rogers et al, 2009) that incorporated a PA counselling component, including: current PA behaviour, decision balance exercise; benefits of PA in general and specific to breast cancer survivors; perceived barriers; prompts to seek social support, goal setting, types and intensities of PA (e.g., explanation of light, moderate and vigorous PA with examples specific to participants, such as taking a brisk walk so that you are mildly breathless but can still hold a conversation); safety advice. We also provided basic lifestyle information such as basic dietary information, portion size, fat intake, smoking, and hydration in generally and during PA.…”
Section: Home-based Pa Interventionmentioning
confidence: 93%